'Hidden' expatriates: international mobility in the United Arab Emirates as a challenge to current understanding of expatriation. (8th March 2017) - Haak‐Saheem, Washika; Brewster, Chris
Abstract : Expatriates are often assumed to have enhanced terms and conditions and, because that makes them expensive, to be in key managerial or technical specialist roles. Employees who come from abroad and are in more manual or even menial roles are usually referred to as 'migrants'. However, there are millions of people around the world who are not migrants, their intended sojourn in a foreign country is seen by them and their employers as temporary, but their employment contracts are far from advantageous compared with those of locals. These 'hidden' expatriates are brought into focus in the emerging Arab Gulf States. In some of these countries, the population consists mainly of expatriates, with the local population a small minority: These expatriates include many in lower‐management or manual or menial jobs. We demarcate these expatriates from organisationally assigned expatriates, self‐initiated expatriates and migrants. We use qualitative data from such expatriates in the United Arab Emirates to explore the issues this raises for governments, employers and the expatriates – and for our understanding of the phenomenon of expatriation.